PENGHENTIAN PERKARA DENGAN DENDA DAMAI PADA TINDAK PIDANA EKONOMI - Rizal Faharuddin (Al-Adl : Jurnal Hukum, 2024)
AbstractThis study aims to determine the application of peace fines by the Attorney General's Office in the settlement of economic crimes, as well as to find the concept of case termination with peace fines in economic crimes, using progressive legal thinking and restorative justice. The research method used is normative with statutory and comparative approaches sourced from primary data. The results showed that peace fines by the Attorney General in the settlement of economic crimes can be carried out based on Article 35 Paragraph (1) letter K of the Law of the Prosecutor of the Republic of Indonesia, this is an implementation of the principle of Opportunity and the position of the Attorney General as Dominus Litis which has permanent legal force. This is in line with the application of case settlement with the principle of restorative justice which prioritises victim recovery. The concept of case termination with a peace fine for taxation, customs, and economic crimes, is carried out with the principle of restorative justice, which is carried out by taking into account the interests of state revenue, there are no elements of corruption, and with the approval of the Attorney General by considering the impact caused by the criminal act, the costs and benefits of handling the case, as well as the guilty statement of the perpetrator and his willingness to pay a peace fine. The conditions for case termination are that the perpetrator is the first time involved in a criminal offence and there has been a restoration to the original state carried out by the perpetrator of the criminal offence.Keywords: Termination of case; peaceful fine; economic crime.